2008
DOI: 10.1130/ges00159.1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of mantle fabrics beneath the south-central United States: Constraints from shear-wave splitting measurements

Abstract: New shear-wave splitting measurements at permanent broadband seismic stations in the south-central United States reveal the orientation and degree of polarization of mantle fabrics, and provide constraints on models for the formation of these fabrics. For stations on the stable North American craton, correspondence between observed polarization direction of the fast wave and the trend of Proterozoic and Paleozoic structures associated with rifts and orogenic belts implies a lithospheric origin for the observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…For other cratons (e.g., Australia, Greenland, Arabia) such consistency was not observed [e.g., Heintz and Kennett , 2005; Hansen et al , 2006; Ucisik et al , 2008]. Some of the discrepancy may be explained by a component of density‐driven flow in the asthenosphere (e.g., underneath Arabia [ Hansen et al , 2006]; see section 2.3), a modification of the asthenospheric flow field around keels [e.g., Fouch et al , 2000; Eaton et al , 2004; Heintz and Kennett , 2005; Gao et al , 2008], and a significant lithospheric contribution (e.g., Australia [e.g., Simons and van der Hilst , 2003; Heintz and Kennett , 2005] and east Antarctica [ Reading and Heintz , 2008]). Some other reported discrepancies between φ SKS and φ APM may have resulted from the large range of published φ APM [e.g., Heintz et al , 2003; Evans et al , 2006] or from the use of an inappropriate APM model (e.g., NNR in Antarctica [ Reading and Heintz , 2008], or HS2‐NUVEL1A in Africa [ Barruol and Ben Ismail , 2001]).…”
Section: Seismic Anisotropy and Apmmentioning
confidence: 99%
“…For other cratons (e.g., Australia, Greenland, Arabia) such consistency was not observed [e.g., Heintz and Kennett , 2005; Hansen et al , 2006; Ucisik et al , 2008]. Some of the discrepancy may be explained by a component of density‐driven flow in the asthenosphere (e.g., underneath Arabia [ Hansen et al , 2006]; see section 2.3), a modification of the asthenospheric flow field around keels [e.g., Fouch et al , 2000; Eaton et al , 2004; Heintz and Kennett , 2005; Gao et al , 2008], and a significant lithospheric contribution (e.g., Australia [e.g., Simons and van der Hilst , 2003; Heintz and Kennett , 2005] and east Antarctica [ Reading and Heintz , 2008]). Some other reported discrepancies between φ SKS and φ APM may have resulted from the large range of published φ APM [e.g., Heintz et al , 2003; Evans et al , 2006] or from the use of an inappropriate APM model (e.g., NNR in Antarctica [ Reading and Heintz , 2008], or HS2‐NUVEL1A in Africa [ Barruol and Ben Ismail , 2001]).…”
Section: Seismic Anisotropy and Apmmentioning
confidence: 99%
“…The geodynamic implications of SWS observations are complicated by the fact that there is more than one mantle process that can lead to the LPO. For continental areas such as the eastern United States (EUS) that are away from active plate boundaries, the most likely processes include (1) simple shear originated from vertical flow gradient in the asthenosphere which leads to an anisotropy parallel to the flow direction, (2) lithospheric compression resulting in fast orientations consistent with the strike of the mountain belts [ Silver , , ; Fouch and Rondenay , ; Long and Silver , ; Refayee et al , ], and (3) magmatic diking in the lithosphere that can lead to an observable dike‐parallel seismic anisotropy [ Gao et al , , , ; Walker et al , ; Kendall et al , ]. Therefore, elucidating anisotropy‐forming mechanisms for a given area is essential not only for understanding the origin of seismic anisotropy but also for characterizing past or current deformational processes in the mantle especially the existence and direction of mantle flow systems.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical and petrophysical experiments demonstrated that under uniaxial compression, the a axis of olivine turns to be perpendicular to the maximum compressional strain direction; under pure shear, it becomes perpendicular to the shortening direction; and under progressive simple shear, it aligns in the flow direction [ Ribe and Yu , 1991; Chastel et al , 1993; Zhang and Karato , 1995]. Therefore the fast polarization direction for the asthenosphere reflects the flow direction, as observed in ocean basins [ Wolfe and Solomon , 1998] and continental rifts and passive margins [e.g., Sandvol et al , 1992; Gao et al , 1994, 1997, 2008]. For the lithosphere, ϕ is mostly parallel to the strike of compressional zones, as observed in many places on Earth [ McNamara et al , 1994; Liu et al , 1995; Silver , 1996; Barruol and Hoffmann , 1999; Fouch and Rondenay , 2006; Li and Chen , 2006].…”
Section: Introductionmentioning
confidence: 99%